Examining Singapore’s State Responsibility in International Law Perspective for the Death of David Hartanto: A Case Study of an Indonesian Citizen in Singapore's Territorial Territory - Ratih, Ayuk Nila; Kusuma, Hanityo Akbar (Faculty of Law, Universitas Negeri Semarang, 2024)
This paper delves into the complex legal and ethical dimensions surrounding the death of David Hartanto, an Indonesian citizen, within the territorial boundaries of Singapore. Hartanto's tragic demise sparked significant attention and debate, raising questions about Singapore's obligations under international law regarding the protection of foreign nationals within its jurisdiction. Drawing upon legal principles, case law, and relevant international agreements, this study scrutinizes Singapore's state responsibility concerning the death of Hartanto. It analyzes the circumstances leading to his demise, investigates potential breaches of legal obligations by Singaporean authorities, and evaluates the adequacy of the legal frameworks governing the protection of foreign nationals. Moreover, the paper explores the broader implications of this case for diplomatic relations, human rights protections, and the rule of law in the context of transnational incidents involving state responsibility. By critically examining the Hartanto case, this paper contributes to the ongoing discourse on the intersection of state sovereignty, human rights, and international legal obligations, offering insights into avenues for enhancing accountability and ensuring the protection of individuals irrespective of their nationality within a state’s territorial jurisdiction.